Implementation of Paperless System for Documentation Process Efficiency at PT Everbright - Irwan Syahputra; Muhammad Iqbal (BIOS: Jurnal Informatika dan Sains, 2024)
PT Everbright faces challenges in managing documentation that still relies on a paper-based system, resulting in inefficiencies in storing, searching, and distributing documents. This system also increases operational costs and increases the risk of document loss or damage. Therefore, this study aims to implement a paperless system at PT Everbright to improve the efficiency of the documentation process. By utilizing digital technology, such as document management software and electronic filing systems, companies can reduce dependence on paper, accelerate information access, and optimize internal workflows. This study evaluates the effectiveness of implementing a paperless system in reducing the time required for document searches, minimizing document management errors, and reducing operational costs. The expected results are increased efficiency, reduced costs, and contributions to environmental sustainability through reduced paper use. Thus, the paperless system is expected to provide a solution for PT Everbright to achieve a more efficient, safe, and environmentally friendly documentation process.